Utilization of Cauliflower Stems and Leaves Powder in the Development of High Fibre Spent Hen Meat Cutlets - Kaur, Simranjeet; Goswami, Mayank; Kumar, Pavan; Mehta, Nitin; Sharma, Amit (Journal of Meat Science, 2022)
The present study was envisaged to develop high fibre spent hen meat cutlets by utilizing stems and leaves powder of cauliflower (CLSP) at four different levels viz. Control-0%, T1-2%, T2-4% and T3-6%, by replacing lean meat in the basic formulation. The developed meat cutlets were analyzed for various physicochemical, proximate, instrumental colour, texture and sensory attributes. Moisture, cooking yield, ash and fibre content recorded a significant (p<0.05) increase whereas pH and fat content followed a significant (p<0.05) decreasing trend in CLSP incorporated spent hen meat cutlets. Dimensional parameters such as height expansion and length/breadth shrinkage improved significantly (p<0.05) in all the treatments containing CSLP compared to control. Color values viz. L* and b* values recorded a significant (p<0.05) increase whereas a* values followed the decreasing trend with increasing levels of CLSP in meat cutlets. CLSP incorporation resulted in significant (p<0.05) improvement in the textural profile of meat cutlets. The overall acceptability scores of spent hen meat cutlets decreased significantly (p<0.05) with the addition of CSLP at a 6% level as compared to the other two treatments and control, due to the masking of meat flavor by vegetable source. Thus, fibre fortified spent hen meat cutlets having good acceptability and high nutritive value could be prepared by utilizing cauliflower waste (stems and leaves powder) at a 4% level of lean meat replacement, as it is a good source of dietary fibre and beta-carotene.